2013
DOI: 10.1111/tra.12059
|View full text |Cite
|
Sign up to set email alerts
|

Flotillins Regulate Membrane Mobility of the Dopamine Transporter but Are Not Required for Its Protein Kinase C Dependent Endocytosis

Abstract: SUMMARY Flotillins were proposed to mediate clathrin-independent endocytosis, and recently, flotillin-1 was implicated in the protein kinase C (PKC)-triggered endocytosis of the dopamine transporter (DAT). Since endocytosis of DAT was previously shown to be clathrin-mediated, we re-examined the role of clathrin coat proteins and flotillin in DAT endocytosis using DAT tagged with the hemagglutinin epitope (HA) in the extracellular loop and a quantitative HA antibody uptake assay. Depletion of flotillin-1, floti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(61 citation statements)
references
References 54 publications
(108 reference statements)
2
57
2
Order By: Relevance
“…Importantly, the variant displayed reduced association with flotillin-1 as well as reduced membrane raft localization, quantified on the basis of colocalization with fluorescent Ctxb labeling of GM1 ganglioside. These findings echo the trafficking insensitivity to PKC activation observed by Cremona et al (2011) with loss of flotillin-1 or its mutation, as well as the increase in basal endocytosis observed by Sorkina et al (2013) with the end result being dependent, perhaps, on technical considerations such as cell hosts and levels of expression. Interestingly, the DAT Cys615 mutant still supports AMPH-evoked DA efflux (Sakrikar et al, 2012) and thus may be useful in further segregating PKC-dependent control of trafficking versus function.…”
Section: Regulation Of Dopamine Transporter Membranesupporting
confidence: 67%
See 2 more Smart Citations
“…Importantly, the variant displayed reduced association with flotillin-1 as well as reduced membrane raft localization, quantified on the basis of colocalization with fluorescent Ctxb labeling of GM1 ganglioside. These findings echo the trafficking insensitivity to PKC activation observed by Cremona et al (2011) with loss of flotillin-1 or its mutation, as well as the increase in basal endocytosis observed by Sorkina et al (2013) with the end result being dependent, perhaps, on technical considerations such as cell hosts and levels of expression. Interestingly, the DAT Cys615 mutant still supports AMPH-evoked DA efflux (Sakrikar et al, 2012) and thus may be useful in further segregating PKC-dependent control of trafficking versus function.…”
Section: Regulation Of Dopamine Transporter Membranesupporting
confidence: 67%
“…A conflicting study, however, reported that in both HEK-293 and HeLa cells, siRNA knockdown of flotillin-1 failed to block PMA-induced DAT endocytosis and may even slightly enhance DAT internalization. Loss of flotillin-1 did, however, increase the lateral mobility of DAT in the membrane as measured by a fluorescence recovery after photobleaching (FRAP) assay, suggesting that flotillin-1 may play a role in anchoring DAT, within membrane raft microdomains (Sorkina et al, 2013). The role PKC plays in the interactions between DAT and flotillin-1/membrane rafts still remains unclear; however.…”
Section: Regulation Of Dopamine Transporter Membranementioning
confidence: 98%
See 1 more Smart Citation
“…For example, flotillin-1 and DAT can be co-immunoprecipitated in HEK293 cells [45,46]. DAT and flotillin partition in similar detergent-resistant membrane fractions [41,45] and depletion of flotillin shifts DAT localization to non-rafts [45].…”
Section: Sphingolipids and Gangliosidesmentioning
confidence: 99%
“…DAT and flotillin partition in similar detergent-resistant membrane fractions [41,45] and depletion of flotillin shifts DAT localization to non-rafts [45]. Flotillin facilitates PKC-mediated DAT internalization in HEK293 cells [45]; however, it was also reported that flotillin knockdown via siRNA does not alter PKC-mediated DAT trafficking [46]. Additionally, DAT physically interacts with Rin, a Ras-like GTPase, and they form a complex in lipid raft microdomains of rat PC12 cells [47].…”
Section: Sphingolipids and Gangliosidesmentioning
confidence: 99%